Regional disparities in Romania – an analysis on the foreign direct investments efficiency - Dan Marius, Voicilas; Todorović, Ljubiša; Damnjanović, Radovan (Economics of Agriculture, 2010)
By this study, we intend to analyze the evolution of the Romanian regions during transition under the influence of the foreign direct investment (FDI) inflows, using the efficiency calculations of the macroeconomic indicators. The methodology developed by Romanu & Vasilescu (1993) was chosen because it reflects, in a direct way, the contribution of the investments on the evolution of the macroeconomic indicators and in which way the FDI influenced their evolution. The ratio between the variation of the indicators of effort and effects shows us the efficiency and the progress of an effect indicator for every additional value of effort. We consider as effort indicator the FDI level and effect indicators the gross domestic product (GDP), gross value added (GVA) and fixed gross capital formation (FGCF). If we have in view these premises, the evolution of the Romanian economic development regions is characterized by huge disparities. The most obvious is between Bucharest and the rest of the regions. In the same time, FDI had strong positive influences on the macroeconomic indicators and the activity was efficient only after 2000.